Stereomicroscope with Imaging Analysis: A Versatile Tool for Wetting, Gel Formation and Erosion Rate Determinations of Eutectic Effervescent Tablet - Pornsit Chaiya; Siriporn Okonogi; Thawatchai Phaechamud (MDPI AG, 2022)
Wettability, gel formation and erosion behaviors could influence the drug release pattern of solid dosage forms. Typically, these parameters are evaluated using a variety of techniques. Nonetheless, there has been no previous research on versatile tool development for evaluating several tablet characteristics with a single tool. The aim of this study was to develop the versatile tool for measuring various physical properties of eutectic effervescent tablets and also investigate the relationship between these parameters with parameters from drug dissolution. Ibuprofen (IBU)-poloxamer 407 (P407) eutectic effervescent tablets were fabricated with a direct compression method. Their wetting properties, gel formation and erosion behaviors were investigated using a stereomicroscope with imaging analysis in terms of the liquid penetration distance, gel thickness and erosion boundary diameter, respectively. In addition, the dissolution rate (k) and disintegration time of eutectic effervescent tablets in 0.1 N HCl buffer pH 1.2 were also determined. Incorporation of P407 into the IBU tablet improved the tablet wetting properties with increasing liquid penetration distance under stereoscope. CO2 liberation from effervescent agents promoted tablet surface roughness from matrix erosion. The relationship between observed physical properties and disintegration and dissolution parameters suggested that the combination of erosion by effervescent agents and gel formation by P407 had a potential influence on dissolution enhancement of the formulation. Therefore, a developed stereomicroscope with an imaging analysis technique was exhibited as an alternative versatile tool for determining the wetting properties, gel formation and erosion behaviors of pharmaceutical solid dosage forms.